ISCHEMIC STRIATED MUSCLE AS AN INDICATOR OF THE ACTIVITY OF A CARDIAC GLYCOSIDE - POZO, EFREN C DEL; PARDO (INSTITUTO DE SALUBRIDAD Y MEDICINA TROPICAL, CD. MEXICO, DF, MEX, 1979)
A study was made of the effects of k-strophanthoside on the contractions of the gastrocnemius-soleus-plantaris muscles made ischemic by intermittent occlusion of the aorta in cats anesthetized with Dial. The intravenous injection of 0.1 to 0.2 mgm. per kg
J PHARMACOL EXP THER
Keywords: ISCHEMIC, STRIATED, MUSCLE, CARDIAC, GLYCOSIDE; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA